Modified EP/sin for Optimal Power Flow with Economic Dispatch - Chansareewittaya, Suppakarn (Srinakharinwirot University Engineering Journal, 2019)
In this paper, evolutionary programming is modified for improve optimal power flow and economic dispatch problem. First improvement is to enhance power transfer capability of power transactions between generators and load buses. Second improvement is to determine ratio of max power transfer capability per economic dispatch. Both improvements are evaluated under optimal power flow concepts and optimal allocation of unified power flow controller. Particular optimal allocation of unified power flow controller includes optimal location and parameter settings. This optimal allocation is determined by this modified evolutionary programming. The main of modifying is to place value of sine function in mutation method. The IEEE 30-bus test system is used as tests system. Test results show that the proposed method gives the optimal allocation of unified power flow controller which makes the better overall results of optimal power flow with economic dispatch than original evolutionary programming.